Virulence analysis of wheat stem rust (Puccinia graminis f. sp. tritici) in Horro Guduru Wollega, Western Ethiopia - Abdissa, T.; Fininsa, C.; Abeyo, Bekele G.; Woldeab, G. (Wiley, 2022)
Stem rust caused by Puccinia graminis f. sp. tritici is one of Ethiopia's most serious wheat diseases. Because of mutation and genetic recombination, stem rust can rapidly evolve new virulence to resistant genes. The Ethiopian highlands are well-known hotspots for the rapid emergence and spread of new wheat stem rust races. The objective of this study was to determine the virulence diversity and spatial distribution of Pgt races in the main wheat-growing districts, Horro Guduru Wollega. Wheat stem rust samples were collected from Abay Chomen, Amuru, Guduru, Hababo Guduru, Horro, Jardaga Jarte, Jimma Ganati and Jimma Rare districts during the main cropping seasons of 2015 and 2016. In the study, 147 stem rust isolates were derived from 121 viable samples. The physiological races of stem rust were determined on seedlings of standard wheat stem rust differentials using the International System of nomenclature. Twelve (12) physiological races of stem rust were identified. TKTTF, TTKSK, JRCQC, TRTTF and TTTTF were the most common in all districts with a frequency of 53.1%, 15.6%, 14.3%, 6.8% and 2.7%, respectively. TKTTF and TTKSK, two highly virulent races, were found in all districts. Four stem rust resistance genes (Sr11, Sr31, Sr36 and SrTmp) confer resistance to the majority of the virulent races identified. Sr24 was effective against all virulent races in this study but ineffective against the Ug99 variant (race TTKTT) detected in the country. The findings could be helpful for breeders to select many effective resistance gene combinations to provide more durable stem rust resistance.